Prevalence of and factors associated with symptoms consistent with a diagnosis of irritable bowel syndrome among resident physicians in standardised training in China: a cross-sectional study - Xin Wang; Ning Li; Xia Li; Zhigang Li; Jun Zhao; Xuefei Wang; Xin Hao; Jiayi Yang; Junjian Tian (BMJ Open)
Objectives This study aims to investigate the incidence of and factors associated with irritable bowel syndrome (IBS) among resident physicians in standardised training at eight traditional Chinese medicine (TCM) hospitals in China.Design A cross-sectional survey was administered to resident physicians in their first to third years of standardised training at eight TCM hospitals.Participants and setting A total of 514 resident physicians in standardised training were included.Measures The questionnaire consisted of two sections, namely: section A collected basic information, and section B included the four-item Perceived Stress Scale (PSS-4), the Patient Health Questionnaire-4 (PHQ-4), the Pittsburgh Sleep Quality Index (PSQI) and the Rome IV criteria for IBS. Univariate and multivariate logistic regression models were constructed to assess the associations of age, sex, body mass index, stress, depression, anxiety, sleep quality and IBS.Results Of the included resident doctors, 77.2% were female, 20.4% were obese or underweight and 8.6% had symptoms consistent with a diagnosis of IBS. There were no statistically significant differences in lifestyle factors (night shift work, overtime work or working efficiency during the COVID-19 pandemic) between patients with IBS and participants without IBS (hereafter, non-IBS participants) (p=0.429, p=0.572 or p=0.464, respectively). Notably, compared with non-IBS participants, patients with IBS had significantly higher mean scores on the PSS-4 and PHQ-4 (p=0.028 and p=0.012, respectively); however, there was not a significant difference in PSQI scores between these two groups (p=0.079). Depression symptoms were significantly associated with IBS (unadjusted OR 0.498, 95% CI 0.265 to 0.935, p=0.030).Conclusion These findings suggest that IBS is common among resident physicians in standardised training. Future studies should investigate emotional distress, especially stress and depression, in the development of prevention or treatment of IBS.